2021
DOI: 10.1111/apa.16051
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐inflammatory syndrome and Kawasaki disease in children during the COVID‐19 pandemic: A nationwide register‐based study and time series analysis

Abstract: Aim We investigated whether the ongoing COVID‐19 pandemic was associated with the occurrence of Kawasaki disease or with multi‐inflammatory syndrome in children (MIS‐C). Methods This national Finnish register‐based study was based on laboratory‐confirmed severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infections, MIS‐C and Kawasaki disease cases. We performed a time series analysis on the occurrence of Kawasaki disease in 2016–2020. Results In 2020, there were 5170 laboratory‐confirmed COVID‐19 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…We found that neuroimmune complications were exceedingly rare, whereas MIS-C occurred in 0.05% of confirmed SARS-CoV-2 infections, which is similar to other population based estimates. 28 29 30 Previous studies have identified obesity and black and Hispanic race as important risk factors for severe covid-19 and MIS-C. 24 25 30 This needs to be considered when generalising our results, as Denmark is predominantly a society of white ethnicity with a low prevalence of childhood obesity. 31 …”
Section: Discussionmentioning
confidence: 86%
“…We found that neuroimmune complications were exceedingly rare, whereas MIS-C occurred in 0.05% of confirmed SARS-CoV-2 infections, which is similar to other population based estimates. 28 29 30 Previous studies have identified obesity and black and Hispanic race as important risk factors for severe covid-19 and MIS-C. 24 25 30 This needs to be considered when generalising our results, as Denmark is predominantly a society of white ethnicity with a low prevalence of childhood obesity. 31 …”
Section: Discussionmentioning
confidence: 86%
“…Serious complications and, in relatively rare cases, deaths have occurred ( 120 ). Of particular interest, children have occasionally experienced a serious inflammatory syndrome, multisystem inflammatory syndrome in children (MIS-C), following COVID-19 infection ( 121 ). This syndrome is similar in some respects to Kawasaki disease, including Kawasaki disease shock syndrome ( 122 124 ), and is thought to be a distinct clinical manifestation of SARS-CoV-2 due to its distinct cytokine profile and the presence of burr cells in peripheral blood smears ( 125 , 126 ).…”
Section: Clinical Presentation Of Covid-19mentioning
confidence: 99%
“…In both Finland and South Korea, KD incidence rates declined after the implementation of school closures. Datasets from the studies in South Korea and Finland were both obtained from nationwide health registries [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%